The Correlation Between Age of Marriage with Cervical Cancer Incidence in X Hospital Manado - Shintya, Lea Andy (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Cervical cancer is one of the most common cancers affecting women. Marriage at a very young age is suspected to be one of the risk factors for the occurrence of cervical cancer. This study aims to analyze the relationship between the age of marriage and the incidence of cervical cancer. Method: This study uses a case control design with 120 sample respondent using total sampling method. Data were collected through medical records and interviews. Data analysis using the chi-square test. Results: Of the 27 respondents 54 % of women who married at age < 20 years suffered from cervical cancer, while in the age group 20 years, only 23 respondent 46 % cancer cervix. The statistical test results indicate a significant relationship between the age of marriage and the incidence of cervical cancer (p=0.026), with a correlation value of 0.222, which is considered weak as it falls within the range of (0.20-0.399). There is a significant relationship between the age of marriage and the incidence of cervical cancer. Women who marry at age < 20 years have a higher risk of suffering from cervical cancer compared to those who marry at age 20 years. Recommendation future researchers should conduct further studies to identify other factors that play a role in the relationship between marriage age and cervical cancer, and evaluate cervical cancer prevention interventions among women who marry at a young age.